Yearbook of the United Nations 2012. v. 65 (United Nations, 2016)
A principal reference work of the United Nations, providing a comprehensive account of the wide ranging work of UN and the Intergovernmental organizations related to UN during the year covered; includes subject index, index of names and index of resolutions and decisions adopted by General Assembly, Security Council, Economic and Social Council, and Trusteeship Council